Fiscal Rules and the Budget Process - Milesi-Ferretti, Gian (IMF Working Papers; Working Paper ;, 1996)
This paper examines the rationale for the imposition of fiscal rules as a way to reduce budgetary imbalances. It presents theoretical arguments for the existence of a 'fiscal deficit bias' and the empirical evidence on the economic, political and institutional factors leading to this bias. In the context of these findings, it discusses the potential role of legal constraints on the level of key fiscal variables, and of reforms in budgetary procedures in enhancing fiscal discipline. It also evaluates proposals for budgetary reform in Italy.